2022
DOI: 10.3390/nu14142989
|View full text |Cite
|
Sign up to set email alerts
|

Free School Meal Improves Educational Health and the Learning Environment in a Small Municipality in Norway

Abstract: It has been suggested that school meals could have an impact on students’ learning environments; however, existing research in this field is scarce and inconclusive. The purpose of this study was to explore teachers’ and school administrators’ experiences with the introduction of a free school meal and whether this influenced the learning environment. The study was conducted in upper primary and lower secondary schools in a small municipality in Norway. In this qualitative study, 17 informants participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…In the present study, no third-order interactions were found, indicating that the effect of ending the program did not differ according to sex or parental education, which means that there was no difference between boys and girls, or between socioeconomic groups (based on parental education) in this sample. Thus, the findings do not confirm the results of studies showing that free school meals equalize social inequality [15][16][17], but also do not support the studies that show higher FV intake in high socioeconomic groups [12,13].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In the present study, no third-order interactions were found, indicating that the effect of ending the program did not differ according to sex or parental education, which means that there was no difference between boys and girls, or between socioeconomic groups (based on parental education) in this sample. Thus, the findings do not confirm the results of studies showing that free school meals equalize social inequality [15][16][17], but also do not support the studies that show higher FV intake in high socioeconomic groups [12,13].…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, health promotion measures are often more effective among families with a high socioeconomic background, which may contribute to an increase rather than a decrease in health disparities among different socioeconomic groups [14]. However, providing free school meals seems to be one of few effective initiatives contributing to the reduction of the socioeconomic gap [15][16][17]. The importance of free school meals is also emphasized by results from tracking studies indicating that dietary habits established in childhood/adolescence tend to be maintained in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Prioritizing changes based on empirical data could lead to more effective, tailored interventions that could substantially improve the quality of life of students and potentially serve as a model for other regions. Offering a free meal during school [37].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was perceived that if teachers were present in the dining hall, students would be much more likely to try the lunch. Data from school administrators in Norway also suggests that teacher presence during lunch had the additional benefit of strengthening teacher-student relationships [ 30 ]. Research from the US investigating the barriers and facilitators of the implementation of the new National School Lunch programme guidelines from the perspective of food service directors highlighted that teachers need to participate in the food programme [ 31 ].…”
Section: Discussionmentioning
confidence: 99%